The Puzzle of Educated Unemployment in West Africa - Esther Mirjam Girsberger; Romuald Meango (Institute of Labor Economics (IZA), 2022)
Many developing countries exhibit a puzzling pattern given their scarce human capital: unemployment rates increase with education. We develop and estimate a model where educated unemployment arises from heterogeneous workers participating in a frictional labour market with three sectors (public, private and self-employment). We estimate that public sector distortions explain around two-thirds of educated unemployment in urban Burkina Faso and one-quarter in Senegal. We then simulate three equally costly policies. In contrast with public job creation and subsidies to self-employment income, subsidies for private sector vacancy creation effectively reduce educated unemployment and improve aggregate workers' welfare.
Keywords: J24; J64; E24; 330; unemployment; education; search and matching model; urban West Africa